![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
2(x - 3) + 5 = 3x - 1
2x-6+5=3x-1
2x-1=3x-1
2x-3x=-1+1
-x=0
x=0
2x(3x + 2) - 5 = 3( 2x^2 - 2x + 1)
6x2+4x-5=6x2-6x+3
6x2+4x-6x2+6x=3+5
10x=8
x=4/5
(3x - 2)(2x - 3) + 5 = 5
(3x-2)(2x-3)=0
=>3x-2=0 hoặc 2x-3=0
=>x=2/3 hoặc x=3/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2x - 5 = 3 + 2x - 7x
=> 2x - 2x + 7x = 3 +5
=> 7x = 8
=> x = 8/7
b) \(\left(2x-1\right)^2=\left(2x-1\right)^5\)
=> \(\left(2x-1\right)^2-\left(2x-1\right)^5=0\)
=> \(\left(2x-1\right)^2\left[1-\left(2x-1\right)^3\right]=0\)
=> \(\orbr{\begin{cases}\left(2x-1\right)^2=0\\1-\left(2x-1\right)^3=0\end{cases}}\)
=> \(\orbr{\begin{cases}2x-1=0\\\left(2x-1\right)^3=1\end{cases}}\)
=> \(\orbr{\begin{cases}2x=1\\2x-1=1\end{cases}}\)
=> \(\orbr{\begin{cases}x=\frac{1}{2}\\2x=2\end{cases}}\)
=> \(\orbr{\begin{cases}x=\frac{1}{2}\\x=1\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
cho k lấy ko
|2x - 2| - 5 = 2x
<=> |2x - 2| = 2x + 5
Đk : 2x + 5 \(\ge\)0
<=> 2x \(\ge\)-5
<=> x\(\ge\)\(\frac{-5}{2}\)
Khi đó : 2x - 2 = 2x + 5 or 2x - 2 = -2x - 5
<=> 2x - 2 - 2x = 5 or 2x - 2 + 2x = -5
<=> -2 = 5 (vô lý) or 4x - 2 = -5
<=> x \(\in\varnothing\) or 4x = -3
<=> x = \(\frac{-3}{4}\)(t/m ĐK)
Vậy x = -3/4